What works to prevent falls in older adults dwelling in long term care facilities and hospitals? An umbrella review of meta-analyses of randomised controlled trials. Issue 3 (July 2015) - Stubbs, Brendon; Denkinger, Michael D.; Brefka, Simone; Dallmeier, Dhayana
Highlights: Conflicting evidence exists regarding the effectiveness of exercise and vitamin D supplementation to prevent falls in hospital and LTCF settings. The most promising evidence exists for multifactorial interventions in LTCF and hospitals. The methodological quality of MA to date is moderate to high quality. Abstract: Preventing falls in long term care facilities (LTCF) and hospitals is an international priority. Many interventions have been investigated and summarised in meta-analyses (MA) and there is a need to synthesise the top of the hierarchy of evidence in one place. Therefore we conducted an umbrella review of MA of randomised controlled trials (RCTs) of falls prevention interventions LTCF and hospitals. Two independent reviewers searched major electronic databases from inception till October 2014 for MA containing ≥3 RCTs investigating any intervention to prevent falls in LTCF or hospitals in older adults aged ≥60 years. Methodological quality was assessed by the AMSTAR tool and data were narratively synthesised. The methodological quality of the MA was moderate to high across the 10 included MA. Nine MA provided data for LTCF and only two considered hospital settings. Only one MA defined a fall and two reported adverse events (although minor). Consistent evidence suggests that multifactorial interventions reduce falls (including the rate, risk and odds of falling) in LTCF and hospitals. Inconsistent evidence exists for exercise and vitamin D as single interventions in LTCF, whilst no MA has investigated this in hospitals. No evidence exists for hip protectors and medication review on falls in LTCF. In conclusion, multifactorial interventions appear to be the most effective interventions to prevent falls in LTCF and hospital settings. This is not without limitations and more high quality RCTs are needed in hospital settings in particular. Future RCTs and MA should clearly report adverse events.